Decision Making for Boycott Action of Pro-Israel Food and Beverage Products by Bengkulu University Students - Ningrum, Putri Yulia; Nopianti, Heni; Himawati, Ika Pasca (Journal La Sociale, 2025)
The research aims to analyze the decision-making of the boycott of proIsrael food and beverage products carried out by students of the Faculty of Social and Political Sciences, Bengkulu University. The research was conducted using a qualitative approach, and the data collection process was carried out through interviews and observations. The results of the study were analyzed using the theory of social action proposed by Max Weber. Based on the results of interviews submitted by informants, it is obtained that the boycott of pro-Israel products by students of the Faculty of Social and Political Sciences, Bengkulu University is a form of contribution from students to help have a negative impact on the company's performance so that it withdraws its support for Israel. The boycott action carried out by students is due to the emergence of a sense of humanity and feelings of concern, anger, and sadness felt towards the atrocities committed by Israel against Palestine. In addition, boycott actions are also carried out through the dissemination of information with social media as a tool which aims to disseminate information on boycott products and seek the truth of information received from social media such as Tiktok, Instagram, and Twitter. This research is expected to provide deeper insight into the factors that influence student decisionmaking in boycotting pro-Israel products, and can be a reference for academics, educational institutions, and social activists in understanding social care, humanitarian values, and the use of social media in shaping student attitudes towards global issues.